Letters on the surface - Capeto, Rodolfo (InfoDesign, 2007)
Discussing the text/image dichotomy, expressed by the philosopher Vilém Flusser as a dimensional distinction between line and surface, the author proposes that these informational spaces are deeply intertwined along the different perceptual scales involved in their apprehension, implying that the understanding of this relationship may be refreshing for writers and readers.